Pengaruh Prenatal Gentle Yoga Terhadap Penurunan Nyeri Pinggang Bawah Pada Ibu Hamil Trimester III di PMB Bidan Aida Nospita S.Keb Kecamatan LabuhanDeli Kabupaten Deli Serdang Tahun 2023 - Adelia Syntana (STIKES Columbia Asia Medan, 2023)
This study aimed to evaluate the effect of prenatal gentle yoga on reducing lower back pain in third-trimester pregnant women at PMB Midwife Aida Nospita S.Keb in Labuhan Deli District, Deli Serdang Regency, in 2023. The research method employed a quasi-experimental design with treatment and control groups. The study sample consisted of 30 third-trimester pregnant women divided into two groups: one receiving prenatal gentle yoga and the other serving as the control group without yoga intervention. Measurement of lower back pain was conducted before and after the intervention using a visual analog pain scale. The results indicated that prenatal gentle yoga significantly reduced lower back pain in third-trimester pregnant women compared to the control group. In conclusion, prenatal gentle yoga can be an effective alternative in alleviating lower back pain in third-trimester pregnant women.